FAKTOR PENYEBAB PERNIKAHAN DINI ( STUDI KASUS DI DESA HUTATONGA KECAMATAN TAMBANGAN KABUPATEN MANDAILING NATAL ) - Lily Suryani; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in Hutatonga Village, Minangan District, Mandailing Natal Regency with the aim of knowing the causes of early marriage and to find out the attitudes of parents about early marriage at that location. The method used qualitative method. Data collection uses observation an in-def interviews, as well as documentation. The results of this study conclude that many early marriages occur because of mistakes, namely getting pregnant before marriage. So that early marriage has to be done so as not to make something embarrassing. Incidents like this are caused by several factors, namely economic factors, education and parental factors. Besides that, individual factors, namely self-will, and promiscuity that cause pregnancy out of wedlock. The attitude of parents also greatly influences the occurrence of early marriage, because parents are less assertive and pay less attention to their children in the association so that they make children uncomfortable and eventually want to get married and do things that are not good. But in the end, parents begin to accept reality and equip their children with household advice. Keywords : Factors thad cause early marriage and parents’ attitudes towards early marriage actors